Pengaruh Pembelajaran Terpadu Model Tersarang (Nested) Terhadap Pemahaman Konsep Keliling Dan Luas Bangun Datar - Linda Astriani; Iswan (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
This reseach aims to know influence of integrated learning with nested model with conceptual understanding the perimeter and area quadrilaterals. This reseach was conducted at SD Islam Harapan Ibu Pondok Pinang academic year 2018/2019. Randomized control group only design is the methode in this reseach. Subject for this reseach are 55 students consist of 30 students of experimen class and 25 students of control class which is cluster random sampling technique from 5th grade. The instrument used to collect data with essay in 8 questions. The conceptual understanding of the perimeter and area quadrilaterals in experimen class that used integrated learning with nested model includes understanding for scoring translation is 82%, interpretation is 85,3%, and extrapolation is 61,3% even in conventional class for scoring translation is 84,8%, interpretation is 79,3%, and extrapolation is 43,8%. The conclution of this research is the conceptual understanding of the perimeter and area quadrilaterals in experimen class that used integrated learning nested model is better than used conventional learning (thitung = 2,10 > ttabel = 1,68).